2008
DOI: 10.1523/jneurosci.2944-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Magnetic Resonance Imaging Study on the Neural Mechanisms of Hyperalgesic Nocebo Effect

Abstract: Previous studies suggest that nocebo effects, sometimes termed "negative placebo effects," can contribute appreciably to a variety of medical symptoms and adverse events in clinical trials and medical care. In this study, using a within-subject design, we combined functional magnetic resonance imaging (fMRI) and an expectation/conditioning manipulation model to investigate the neural substrates of nocebo hyperalgesia using heat pain on the right forearm. Thirteen subjects completed the study. Results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
182
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 228 publications
(211 citation statements)
references
References 60 publications
(103 reference statements)
22
182
0
4
Order By: Relevance
“…Given that the functional imaging findings were primarily located in the affective-cognitive pain pathway, the authors concluded that their results underline the important role of anxiety in this process (Kong et al, 2008). This study was in part consistent with earlier studies (Sawamoto et al, 2000;Koyama et al, 2005;Keltner et al, 2006), namely that during nocebo hyperalgesia, brain activity in the ACC, insula, and operculum increases significantly during nocebo conditions.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Given that the functional imaging findings were primarily located in the affective-cognitive pain pathway, the authors concluded that their results underline the important role of anxiety in this process (Kong et al, 2008). This study was in part consistent with earlier studies (Sawamoto et al, 2000;Koyama et al, 2005;Keltner et al, 2006), namely that during nocebo hyperalgesia, brain activity in the ACC, insula, and operculum increases significantly during nocebo conditions.…”
Section: Introductionsupporting
confidence: 86%
“…Given that most groups found that the nocebo effect may be produced through a cortical network responsible for affective/ emotional and cognitive aspects of pain perception (Kong et al, 2008), we also obtained skin conductance levels of all participants on days 1, 8, and 90 to assess the arousal in response to painful stimulation. On days 1 and 90, there was no difference of skin conductance between groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that nocebo hyperalgesic manipulations heighten HPA activity (Benedetti et al 2006, Johansen et al 2003, cortical activity in pain-related regions (Kong et al 2008;Bingel et al 2011;Schmid et al 2015), pain-related activity in the spinal 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 cord (Geuter & Buchel 2013), blood pressure and reported negative emotions combined with increased pain reports. The findings from the present study further add that successful induction of nocebo expectations increase negative emotions significantly enough to engage physiological and motivational defense systems (Grillon et al 1991), that enhance cortical alertness measured by startle responses.…”
Section: Discussionmentioning
confidence: 99%
“…Cortical areas that are known to be involved in the processing of negative emotions, such as the amygdala (Schmid et al 2015) and the hippocampus (Kong et al 2008;Bingel et al 2011) were shown to be affected by nocebo manipulations. However, only one prior study has directly tested the assumption that nocebo hyperalgesic suggestions increase negative emotions that, in turn, predict increases in pain .…”
Section: Introductionmentioning
confidence: 99%